Analyzing Communication Strategies KPU Sergai Podcast as Digital Public Communication for Electoral Education - Yohana Yulianti Simbolon (INJECT (Interdisciplinary Journal of Communication), 2026)
This study examines the KPU Sergai Podcast as a digital public communication initiative for voter education. While podcasts offer potential to enhance political literacy through flexible and narrative-driven formats, their effectiveness in institutional contexts remains limited. This research employs a qualitative case study approach, integrating podcast analytics, content observation, and in-depth interviews to analyze how communication strategies are designed and implemented. The findings reveal that podcast performance remains suboptimal, as indicated by consistently low audience reach (fewer than 100 views per episode) and minimal engagement, including limited likes and the absence of comments and shares. These patterns suggest that the podcast has not succeeded in expanding its visibility or fostering interactive communication. Beyond descriptive results, the study identifies a structural communication problem. Internal constraints such as limited resources, lack of technical capacity, and restricted production quality shape content characteristics and distribution strategies, resulting in predominantly one-way communication and misalignment with audience preferences, particularly among younger users. The findings demonstrate a causal pathway in which these constraints lead to audience misalignment, low engagement, and passive audience behavior. This condition reflects a broader communication gap between the interactive potential of digital media and its practical implementation in governmental communication. This study contributes by offering an integrated analytical framework linking institutional capacity, content strategy, and audience engagement. Practically, it highlights the need for more interactive content, multi-platform distribution, and improved production quality to enhance digital public communication effectiveness.